2021
DOI: 10.1051/e3sconf/202126404004
|View full text |Cite
|
Sign up to set email alerts
|

The spraying process simulation of the low-volume sprayer working body

Abstract: The article presents the developed mathematical models that describe the process of spraying the working body of a low-volume sprayer. Theoretical studies show that with an increase in the supply of working fluid to the atomizing disc, the rotational speed of the pneumatic disc atomizer decreases, and in order to ensure the effect of the air flow on the droplet formation process, the radius of the disc should be larger than the radius of the base of the cone-shaped fairing, but less than its maximum critical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The choice of the optimal values of these parameters was carried out on the basis of a symmetrical compositional plan [25][26]. The maximum value of the installation angle of the rotary device relative to the tree trunk is  70 .…”
Section: Optimization Of the Sprayer Parameters For The Treatment Of ...mentioning
confidence: 99%
“…The choice of the optimal values of these parameters was carried out on the basis of a symmetrical compositional plan [25][26]. The maximum value of the installation angle of the rotary device relative to the tree trunk is  70 .…”
Section: Optimization Of the Sprayer Parameters For The Treatment Of ...mentioning
confidence: 99%
“…Analytical studies of a smooth spray disk with a coaxial air flow showed that with the help of an air flow, it is possible to increase the productivity of drop formation while maintaining the dispersion of drops or to obtain a monodisperse spray [1][2][3] at different liquid flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the cost of monodisperse regimes, additional studies are needed, the results of which should form the basis for the creation of a working body for the Low volume desalination spraying of cotton crops. [8,9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%